Impacts of Climate Change (El Nino, La Nina, and Sea Level) on the Coastal Area of Cilacap Regency - Supriatin, Lilik S.; Martono, Martono (Universitas Muhammadiyah Surakarta, 2016)
This research was conducted to determine the impact of El Nino and La Nina on rainfall as well as the impact of El Nino, La Nina, and sea level on coastal flooding in Cilacap Regency. The methods used in this study were statistical analysis and simulation. The results of this study were El Nino caused diminished rainfall in Cilacap regency between 295 to 1665 mm. Meanwhile, La Nina caused surplus rainfall between 189 - 691 mm/year in compared with annual climatological rainfall. When ENSO phenomenon (El Nino) occurred, it caused sea level anomaly to fall, including in 1994, 1997, and 2002 of -11.63 cm, -11.5 cm, and -4.95 cm, respectively. Meanwhile, in La Nina years in 1999 and 2000, theÂ sea level anomaly enhanced by Â 2.55 cm and 5.03 cm, respectively. The result of sea level projection by employing simulation model in this study was compared with the simulation results of the IPCC that obtained a correlation coefficient r of 0.99. Based on the simulation results, the 8 (eight) sub-districts in Cilacap Regency located in the coastal area potentially endure flood due to the impacts of global warming and La Nina with a diverse predicted year of occurrence depending on the altitude of each sub-district.